Analisis Kepuasan Pelanggan terhadap Pelayanan Petugas Transjakarta - Nabila Calista; Dya Anggun Yunita Arifin; Dita Salsabilla Putri; Siti Ballis Nihayatuzzain; Fitri Amalia (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Efficient and high quality public transportation is an important factor in overcoming traffic congestion problems in metropolitan areas. Transjakarta, as one of the largest mass transit systems in Indonesia, plays a key role in providing reliable transportation services for the people of Jakarta. Customer satisfaction with Transjakarta officer services is a crucial factor in ensuring the success and sustainability of this system. This research aims to analyze the level of customer satisfaction with the quality of service provided by Transjakarta officers. By using quantitative methods and collecting primary data through online questionnaires as well as secondary data from related sources, this research evaluates various aspects of service, such as friendliness, speed of response, and clarity of information provided by officers. The results of this analysis are expected to provide valuable insights for Transjakarta in identifying areas that require improvement and devising strategies to increase overall customer satisfaction, thereby maintaining loyalty and competitiveness in the public transportation industry.